2015
DOI: 10.1186/s12870-014-0322-3
|View full text |Cite
|
Sign up to set email alerts
|

Composition, variation, expression and evolution of low-molecular-weight glutenin subunit genes in Triticum urartu

Abstract: BackgroundWheat (AABBDD, 2n = 6x = 42) is a major dietary component for many populations across the world. Bread-making quality of wheat is mainly determined by glutenin subunits, but it remains challenging to elucidate the composition and variation of low-molecular-weight glutenin subunits (LMW-GS) genes, the major components for glutenin subunits in hexaploid wheat. This problem, however, can be greatly simplified by characterizing the LMW-GS genes in Triticum urartu, the A-genome donor of hexaploid wheat. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Compared to the Wcor15-2A2 sequence, the Wcor15-2A1 sequence showed much higher identity (100%) with the Wcor15-2A sequences from tetraploid and hexaploid wheats, suggesting that the T. urartu might be the direct donor of the Wcor15-2A in common wheat and that Wcor15-2A gene from A genome has no mutation during two sequential allopolyploidization events from T. urartu to tetraploid and hexaploid wheats. The result is consistency with the previous studies 23 24 52 . However, taking into consideration of no amplicon from T. monococcum and T. boeoticum when using Wcor15A primer, it suggested that non-coding regions of Wcor15-2A1 were obviously different from Wcor15-2A2 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to the Wcor15-2A2 sequence, the Wcor15-2A1 sequence showed much higher identity (100%) with the Wcor15-2A sequences from tetraploid and hexaploid wheats, suggesting that the T. urartu might be the direct donor of the Wcor15-2A in common wheat and that Wcor15-2A gene from A genome has no mutation during two sequential allopolyploidization events from T. urartu to tetraploid and hexaploid wheats. The result is consistency with the previous studies 23 24 52 . However, taking into consideration of no amplicon from T. monococcum and T. boeoticum when using Wcor15A primer, it suggested that non-coding regions of Wcor15-2A1 were obviously different from Wcor15-2A2 .…”
Section: Discussionsupporting
confidence: 93%
“…The study on origin of A, B and D genomes of bread wheat has been a hot topic. Understanding the origin of hexaploid wheat would benefit not only the genetic diversity but also expand the genetic basis for wheat breeding 23 42 . Previous studies have demonstrated that the sequence data of conserved gene can be used to study the evolution of gene families from different species 43 44 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, T. urartu, as A-genome donor of common wheat, carried two new alleles Glu-3A.3c and Glu-3A.3d. In the present study, the number of allelic variants exceeded that found by Zhang et al (2013) in common wheat, or by Wang et al (2010), Ahmadpoor et al (2014), Ahmadi and Pour-Aboughadareh (2015), Luo et al (2015) and Cuesta et al (2017) in wild relatives of wheat. The development of allele-specific markers is based on the polymorphisms of nucleotide sequences among different alleles, and the relationship between markers and phenotypes needs to be established.…”
Section: Discussioncontrasting
confidence: 56%
“…Additionally, some alleles are not reliably distinguished by this method. 2-DGE in which proteins are separated according to isoelectric point (pI) and molecular mass (MW) has been used to distinguish many but not all LMW-GS alleles and the increased resolution of 2-DGE has resulted in the identification of new alleles not observed by SDS-PAGE ( Ikeda et al 2006 , Lee et al 2016 , Liu et al 2010 , Luo et al 2015 , Zhang et al 2012 , Zhen et al 2014 ). PCR is a much simpler technique and primers specific for many alleles at the Glu-A3 and Glu-B3 loci have been developed and are currently used in breeding programs ( Wang et al 2009 , 2010 , Zhang et al 2004 , 2012 , Zhao et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%